2006
DOI: 10.1093/ndt/gfl247
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease post-liver transplantation

Abstract: Moderate CKD was very prevalent. We identified the risk factors for progression of CKD and also that severe CKD was associated with reduced patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 39 publications
4
85
2
3
Order By: Relevance
“…1,[5][6][7][8] This wide range is partly explained by a lack of consensus criteria as to what constitutes CKD in these populations and by shortcomings of estimating equations that depend on serum creatinine. 9 Transplant candidates and recipients often have lower muscle mass and less creatinine generation than the populations in which these equations were developed, limiting the accuracy of the equations.…”
Section: Prevalence Of Ckd After Nonrenal Organ Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…1,[5][6][7][8] This wide range is partly explained by a lack of consensus criteria as to what constitutes CKD in these populations and by shortcomings of estimating equations that depend on serum creatinine. 9 Transplant candidates and recipients often have lower muscle mass and less creatinine generation than the populations in which these equations were developed, limiting the accuracy of the equations.…”
Section: Prevalence Of Ckd After Nonrenal Organ Transplantationmentioning
confidence: 99%
“…More recently, using the Kidney Disease Outcomes Quality Initiative (KDOQI) classification system, O'Riordan et al 8 examined the risk for CKD by stage among 230 liver recipients who were followed for a mean of approximately 6 yr. Overall point prevalences of CKD among survivors at 10 yr was 2.26% with stage 5, 6.11% with stage 4, 56.77% with stage 3, 23.71% with stage 2, and the rest with minimal or no renal function deficit.…”
Section: Prevalence Of Ckd After Nonrenal Organ Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…19 On the other hand, the female gender has been identified by other authors as more commonly associated with CKD post-LT than males. 2,20,22,23 These non-modifiable factors should be used to help identify patients at higher risk of CKD in our population of post-LT patients.…”
Section: B Discussionmentioning
confidence: 99%
“…8 Importantly, several series have shown that liver transplant recipients who develop chronic renal failure have worse outcomes than those who do not. [8][9][10] Kidney biopsy samples from liver transplant recipients with impaired renal function in the long term have shown that interstitial fibrosis and glomerular sclerosis may each be present in 45%. 11 Calcineurin inhibitor (CNI)-induced arteriolopathy may also be present in approximately 45% of these patients 5 years after transplantation.…”
Section: Continuing Burden Of Impaired Renal Function After Liver Tramentioning
confidence: 99%